2019
DOI: 10.1001/jamapsychiatry.2019.2850
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Association of Endophenotypes for Schizophrenia From the Consortium on the Genetics of Schizophrenia (COGS) Study

Abstract: IMPORTANCE The Consortium on the Genetics of Schizophrenia (COGS) uses quantitative neurophysiological and neurocognitive endophenotypes with demonstrated deficits in schizophrenia as a platform from which to explore the underlying neural circuitry and genetic architecture. Many of these endophenotypes are associated with poor functional outcome in schizophrenia. Some are also endorsed as potential treatment targets by the US Food and Drug Administration. OBJECTIVE To build on prior assessments of heritability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
66
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 79 publications
1
66
0
1
Order By: Relevance
“…In the amygdala, the Hcn1 gene has been identified as a quantitative trait locus for fear learning [44]. Genome-wide association studies (GWAS) have not previously implicated HCN1 in alcohol use disorders, but other GWAS studies have found that HCN1 is associated conditions like schizophrenia and depression, which are known to be comorbid with AUDs [45]. Medications directed at the HCN channel modulation are currently being developed for seizure activity [46] and may prove useful in treating symptoms associated with AUDs associated with withdrawal-related excitability.…”
Section: Discussionmentioning
confidence: 99%
“…In the amygdala, the Hcn1 gene has been identified as a quantitative trait locus for fear learning [44]. Genome-wide association studies (GWAS) have not previously implicated HCN1 in alcohol use disorders, but other GWAS studies have found that HCN1 is associated conditions like schizophrenia and depression, which are known to be comorbid with AUDs [45]. Medications directed at the HCN channel modulation are currently being developed for seizure activity [46] and may prove useful in treating symptoms associated with AUDs associated with withdrawal-related excitability.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study indicate that GCNT1 and its interacting factors may function via fatty acid related pathways, which promote the development of prostate cancer among people who intake higher amount of omega-6 fatty acids. Besides prostate cancer, gene GCNT1 has previously been linked to neural phenotypes, including the cranial width [62] and cognitive measurements [63]. ASTN2, another gene which interacts with GCNT1, also has demonstrated associations with neural phenotypes including attention-deficit/hyperactivity disorder (ADHD) [64,65], autism spectrum disorders (ASD) [65], neuronal development [65,66], and Alzheimer's disease [67].…”
Section: Discussionmentioning
confidence: 99%
“…Viewed as potential intermediate or “endo” phenotypes (Gottesman & Gould, 2003), such trait‐like psychological constructs are as complex as IDs themselves (Flint, Timpson, & Munafo, 2014). Nonetheless, endophenotypes offer potential developmental insights into psychopathology when their latent structure is examined (Kendler & Neale, 2010) and have recently shown promise for dissecting molecular genetic components of mental illness (Greenwood et al, 2019). Early studies support subsets of measures that index shared or specific components of genetic risk for IDs (reviewed in Savage, Sawyers, Roberson‐Nay, & Hettema, 2016).…”
Section: Introductionmentioning
confidence: 99%